GalNAc-containing neoglycoconjugates having various geometries and valencies: Syntheses and their lectin binding studies. - Kim, Jin Mi. (University of Ottawa (Canada), 1998)
A series of scaffolding glycoconjugates were synthesized with various carbohydrate densities, conformations, and interglycosidic spacers. These compounds include glycopeptoids, glycocalix[4]arenes, self-assembled glycoclusters and glycodendrimers, glyco PAMAM dendrimers, and glycopolymers. The synthesis of Tn-antigen glycopeptidomimetic clusters, peptoids (N-substituted oligoglycines), was accomplished to generate metabolically stable glycopeptide analogs in multivalent fashion. By reiteration of the deprotection-coupling process using monomer and dimer as building blocks, trimer and tetramer were synthesized. Hexamer and octamer were obtained in the same manner. Whereas glycopeptoids are arranged in linear fashion, structurally more defined, tree-like glycodendrimers were synthesized utilizing GaINAc derivatives as carbohydrate entities and calix[4]arene as a core to afford tetra-, octa-, and hexadecamers. Two tetramers, each having four equidistant GaINAc residues, with different lengths of spacer arms were synthesized by coupling GaINAc ligands to acyl chloride on a p-tert-butylcalix[4]arene core. Glycocalix[4]arenes with higher valencies, octa- and hexadecamers were obtained using a double N-alkylation strategy. This strategy was extended to synthesize glyco PAMAM dendrimers. The second generation (G2), StarburstRTM PAMAM core was dialkylated with bromoacetylated GaINAc derivatives to afford 32-mers. A more convenient alternative to long and iterative procedures to construct hyperbranched glycodendrimers evaluated nucleated simple building blocks (dendrons) around metal ions. The synthesis of small building blocks and their non-covalent assembly around the metal ions, Fe(II) and Cu(II) were described. Preparations of enzymetically stable C-glycosides of GaINAc were also presented. O-Acetyl protected galactal was azido-phenylselenylated and Keck allylation at the anomeric center afforded alpha-linked C-glycosides. Elongated C-glycosyl derivatives were used to synthesize small and rigid glycoclusters to investigate the cross-linking properties of Vicia villosa B4 (VVA) lectin. Turbidimetric assays confirmed the ability of the glycodendrimers to cross-link and precipitate the lectin. Solid phase enzyme-linked lectin assay (ELLA) of all the synthesized glycoconjugates showed improved inhibitory efficacy compared to allyl alpha-D-GaINAc which was used as a reference.
Keywords: Chemistry, Organic.